2010
DOI: 10.1148/rg.306105504
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Congenital and Developmental Abnormalities of the Gastrointestinal Tract in Adolescents and Adults: Evaluation with Multimodality Imaging

Abstract: There is a wide variety of congenital anomalies that may affect the gastrointestinal tract. Most symptomatic congenital anomalies are found in newborns and infants. Such anomalies are relatively rare in adolescents and adults, and they may be difficult to identify because clinical symptoms often are nonspecific and insidious, causing them to be mistaken for other common abdominal conditions. Multimodality imaging is useful in evaluating congenital anomalies of the gastrointestinal tract in adults. The imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 42 publications
(111 reference statements)
1
84
1
7
Order By: Relevance
“…Among all enteric duplications, the ones occurring in the gastro-duodenal region are rare accounting for only seven percent of all duplications [1][2][3]. We report an interesting presentation as acute abdomen which turned out to be because of gastric duplication cyst.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Among all enteric duplications, the ones occurring in the gastro-duodenal region are rare accounting for only seven percent of all duplications [1][2][3]. We report an interesting presentation as acute abdomen which turned out to be because of gastric duplication cyst.…”
Section: Introductionmentioning
confidence: 79%
“…Gastro-duodenal duplications are rare [1,2] and account for approximately seven per cent of all gastrointestinal duplication cysts [3].In the era of anomaly scan most of the cysts are detected antenatally, however locating organ of origin may be difficult .Symptomatic presentation depends on the size, position [3]and presence or absence of complications and include gastric outlet obstruction, abdominal pain or an abdominal mass. Embryo pathogenesis of enteric duplications cannot explain occurrence at gatroduodenal region as well as none of the theories quoted in literature have solved the mystery [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal malrotation: Intestinal malrotation occurs when the midgut does not undergo its expected rotation around the axis of the superior mesenteric artery during fetal development [10] . Symptoms of malrotation are most commonly caused by volvulus or obstructing peritoneal bands, which typically manifest during the first year of life [10] .…”
Section: Congenital Abnormalitiesmentioning
confidence: 99%
“…Symptoms of malrotation are most commonly caused by volvulus or obstructing peritoneal bands, which typically manifest during the first year of life [10] . Ultrasound may be performed in the vomiting infant to evaluate for pyloric stenosis and malrotation may be an unexpected finding (Figure 2).…”
Section: Congenital Abnormalitiesmentioning
confidence: 99%
“…Cecal volvulus is not easy to diagnose in many cases and severe necrosis of the affected portion of the intestine may result in the patient's death. Several studies reported the characteristic features of cecal volvulus on radiographic examinations such as barium enema and abdominal computed tomography (CT) [2][3][4][5], but in many cases preoperative diagnosis is difficult.…”
Section: Introductionmentioning
confidence: 99%